2022
DOI: 10.1002/ajmg.a.62950
|View full text |Cite
|
Sign up to set email alerts
|

The diverse pleiotropic effects of spliceosomal protein PUF60: A case series of Verheij syndrome

Abstract: Verheij syndrome (VRJS) is a rare craniofacial spliceosomopathy presenting with craniofacial dysmorphism, multiple congenital anomalies and variable neurodevelopmental delay. It is caused by single nucleotide variants (SNVs) in PUF60 or interstitial deletions of the 8q24.3 region. PUF60 encodes a splicing factor which forms part of the spliceosome. To date, 36 patients with a sole diagnosis of VRJS due to diseasecausing PUF60 SNVs have been reported in peer-reviewed publications. Although the depth of their ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 40 publications
(213 reference statements)
7
15
0
Order By: Relevance
“…The facial features of the patients in our cohort did not fit into a consistent recognizable gestalt, consistent with previous reports (El Chehadeh et al, 2016; Fennell et al, 2022; Low et al, 2017). The most striking facial feature is that of asymmetry which is seen in all the patients in Figure 1 and was noted in previous patients (Low et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The facial features of the patients in our cohort did not fit into a consistent recognizable gestalt, consistent with previous reports (El Chehadeh et al, 2016; Fennell et al, 2022; Low et al, 2017). The most striking facial feature is that of asymmetry which is seen in all the patients in Figure 1 and was noted in previous patients (Low et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is significant given previous reports of two patients with PUF60‐ related developmental disorder also with very narrow external auditory canals (Low et al, 2017). A further case has been reported in the literature of a patient with PUF60‐ related developmental disorder with complete absence of the external auditory meatus (Fennell et al, 2022). Evaluation of these previously reported cases by Low et al (2017), suggested that PUF60 loss of function could contribute to abnormal branchial arch development.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations